The Power of Kalang Woman in Gender Equality (Ancient Javanese Acculturation with Indian Hinduism) - Prabani Setiohastorahmanto Budi; Sugiono Soetomo; Agung Budi ` Sardjono (Celt: A Journal of Culture, English Language Teaching & Literature, 2019)
Kalang is a Javanese sub-ethnic within the Kalang tradition, which is an acculturation of ancient Javanese culture with Hindu culture coming from India. In everyday life, the Kalang women as a mother have a central role in the household activity of being responsible to the husband and children’s well-being. This cultural acculturation still exists in the lives of the Kalang people in Kendal, Central Java, Indonesia. In tradition, Kalang women have power in her position as a housewife, not in using her physical strenght, but to demonstrate the ability to think, manage time and control emotions in carrying out the three household activities of 1) domestic, 2) tradition, and 3) social activity. In today's modern era, gender equality becomes the central talk of how the Kalang society places women within a family that is judged not through the material she obtains, but by her responsibilities.. Through a deductive paradigm with ethnographic techniques, the research finds how powerful a mother is in managing the family. because  she succeeded in showing her role as head of the family, thus perfecting the role of men also as breadwinner, and in making her family life stable by continuously upholding the Kalang tradition.